Assessment and prioritization of community soil and water conservation measures for adaptation to climatic stresses in Makawanpur district of Nepal - Paudel, Prashant; Kafle, Gandhiv (Journal of Wetlands Ecology, 2012)
Climate change is the global concern of our sustainable development whose impact is of great concern to humanity. In Nepal, we are already starting to become aware of recent changes and developing the mechanism to adapt. A study was carried out in Bramha Thakur Community Forest User Group of Makawanpur district with an objective of assessing and prioritizing adaptation options by local community using soil and water conservation measures on climate change. Primary data were collected from direct observation, focus group discussion, key informant interview, preference ranking and transect walk. Meteorological data on temperature and rainfall of 30 years was collected from government sources and climatic trend was analyzed. Prioritization of adaptation options was done using Index of Usefulness of Practices to Adaptation (IUPA) tool developed by Debels et al. (2010). Monthly maximum value of daily maximum temperature and minimum temperature has increased by 0.0461°C and 0.12°C respectively. Numbers of warm days are increasing. Annual precipitation has increased steadily whereas maximum five days and monthly precipitation trend is increasing at high rate, alarming to hazards induced by climate change. Local people were found very resourceful in using various adaptation practices to deal with impacts of climate change. IUPA scoring provided important rankings on the adaptation options. Conservation pond was highly prioritized for drought management. To adapt with flood, engineering structures with or without vegetation were highly used as adaptation option. Bamboo plantation was highly preferred by local community to reduce the impacts of landslide and to prevent its occurrence. Bioengineering structures are highly recommended for long term stability in flooded and landslide affected areas. Further studies on adaptation options and their prioritization in more areas are recommended for comprehensive database and generalization. DOI: http://dx.doi.org/10.3126/jowe.v6i0.6997 J Wet Eco 2012 (6): 44-51